Evaluation of Medication Adherence in Geriatric Patients with Chronic Illnesses in a Tertiary Care Hospital - Manesh, Sneha; Sulthana, Syed Sana; Sirisha, Y; Chauhan, Pappu Kumar (Indian Journal of Pharmacy Practice)
Objectives: Medication adherence is a vital component for treating chronic illnesses. Geriatric patients are often on poly pharmacy this further exacerbates the importance of adhering to the developed drug therapy plan. Non-adherence towards medications in geriatric patients might result in poor health outcomes, new complications, and commodities may worsen which eventually will affect their quality of life hence, it is important to ensure that the right dose is given to the right patient at right time through the right route. Materials and Methods: A prospective cohort study was conducted which comprised of 156 geriatric patients suffering with chronic illnesses were assessed for their medication adherence and quality of life using case report form and other standardized scales like World Health Organization Quality of Life Scale and Morisky medication adherence scale. Results: This study examined 156 patients aged 65 to 75 years. The patients had various past medical histories, such as hypertension, diabetes mellitus, cardiovascular diseases, renal disorders, seizures, mental disorders, pulmonary diseases, cardiac diseases, anemia, gastric and thyroid disorders. High medication adherence was seen in 3%, low medication adherence in 85%, moderate medication adherence in 12%, quality of life was good in 12% and bad in 88%. Results showed that low medication adherence and poor quality of life are more common in elderly patients, and that patient counselling can lead to good medication adherence and good quality of life. Conclusion: This study found that poor medication adherence in geriatric patients with chronic illnesses can affect their quality of life.
Keywords: Medication adherence; Quality of life; Geriatric patients; WHO QOL Scale; Morisky Medication Adherence Scale